Breakfast skipping and depressive symptoms in an epidemiological youth sample in Hong Kong: the mediating role of reduced attentional control - Wong, Stephanie Ming Yin; Choi, Olivia; Suen, Yi Nam; Hui, Christy Lai Ming; Lee, Edwin Ho Ming; Chan, Sherry Kit Wa; Chen, Eric Yu Hai (Frontiers in Psychiatry, 2025)
IntroductionBreakfast skipping is common among young people, although previous work has suggested its negative influences on cognitive and executive functions and mental health outcomes. Whether reduced impulse control, particularly in the cognitive domain, would be a mechanism that links breakfast skipping to elevated psychiatric symptoms remains to be investigated.MethodsWe used data from 3154 young people (aged 15–25 years) in the Hong Kong Youth Epidemiological Study of Mental Health 2019–2022. Participants were asked about their general breakfast consumption habits, impulsivity (overall and its subdomains, using the Barratt Impulsiveness Scale–11), depressive symptoms (Patient Health Questionnaire–9), anxiety symptoms (Generalized Anxiety Disorder Scale–7), and functioning (reduced and lost productivity due to mental health problems, and the observer-rated Social and Occupational Functioning Assessment Scale). Impulsivity and its subdomains were tested for their potential mediating influences between breakfast skipping frequency and symptom outcomes. Sociodemographic variables, psychiatric history, and eating disorder symptoms were adjusted for in all mediation models.ResultsThe weighted prevalence of daily breakfast consumption and breakfast skipping (defined as no breakfast consumption at all) was 33% and 14.2%, respectively. More frequent breakfast skipping was associated with higher levels of impulsivity, specifically in terms of attentional control (r=0.14) and self-control (r=0.13), and depressive symptoms (r=0.14), all p<0.001. Breakfast skipping frequency also showed significant associations with anxiety symptoms and poorer functioning, although their relationships were weak (r range=0.04–0.08). In a parallel mediation model, attentional impulsivity (B=0.21, SE=0.03, CI=0.15–0.27), but not self-control impulsivity (B=0.01, SE=0.01, CI=-0.02–0.03), significantly mediated the relationship between breakfast skipping and depressive symptoms and explained 34.2% of the total effect. All findings remained unchanged even when excluding those who reported rising at 12 pm or after.ConclusionBreakfast skipping is associated with elevated depressive symptoms in young people, with impaired attentional control being an important mechanism in this relationship. Encouraging young people to build regular breakfast habits may be incorporated as part of future lifestyle interventions for mental disorders and be further emphasised in public health policies.